Implementasi Pendidikan Karakter Islami Berbasis Kearifan Lokal dalam Mengatasi Perundungan di SD Negeri Kuripan Watumalang - alya renika utami; Maryono; Fatiatun (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
This study aims to: (1) determine the process of Islamic character education based on local wisdom in preventing bullying at SD Negeri Kuripan Watumalang; (2) analyze its implementation strategies; and (3) identify supporting and inhibiting factors. The study uses a qualitative descriptive approach with field research method. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman's interactive model. Results show that: (1) implementation occurs systematically through three stages: needs-based planning, program execution through Islamic and Javanese local wisdom habituation (unggah-ungguh, gotong royong, musyawarah), and continuous evaluation through principal supervision; (2) strategies are multi-dimensional, encompassing multi-method approaches, empathy cultivation, integration of Javanese cultural values with Islamic akhlakul karimah teachings, ongoing supervision, and active school-family-community partnerships; (3) supporting factors include strong leadership, teacher exemplary conduct, positive school culture, parental involvement, and deeply-rooted local wisdom; inhibiting factors include negative technology and social media influence, diverse family backgrounds, outside peer influence, absence of formal anti-bullying community regulations, and limited school-parent communication.